Meningkatkan Kesadaran Lingkungan dan Pembuatan Profil Desa untuk Pembangunan Berkelanjutan Desa Parimata Kabupaten Barito Kuala - Mutiara Khansa Nabila; Panggih Prabowo Rona Saputra; Anita Grace Napitupulu; Aya Aulia Putri Himmond; Maulidya Sekarwangi; Muhammad Rizcky Ramadhan; Muhammad Rizky Anugrah Fadhillah; Puspa Ananda Putri; Sakinah Mutmainah (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2023)
The waste issue in Indonesia has yet to find the word "finished," especially in Parimata Village, Belawang District, Barito Kuala Regency, South Kalimantan. Both organic and inorganic waste is scattered in residential areas and along the banks of the Barito River. On the other hand, the village government lacks a village profile document, which is crucial for the future development sustainability of the village. Based on these two issues, the Community Service Team has initiated a service program that aligns with producing concrete solutions for Parimata Village. In this community service, the team focuses on raising awareness among the community not to dispose of waste carelessly. The service program includes waste awareness and environmental cleaning actions, household waste socialization, and a demonstration of recycling used cooking oil. The last component is the creation of a village profile document. The program activities were carried out from July 17 to August 20, 2023, using a live-in method. The Community Service Team believes that these three programs can increase community awareness not to dispose of waste carelessly, encourage alternative waste management methods such as recycling, and the presence of a village profile document can assist Parimata Village in developing its potential. Furthermore, these three programs can contribute to the sustainability of Parimata Village in becoming a waste-free village with a community that values high environmental consciousness around them.